PERTANGGUNGJAWABAN KRIMINAL ORANG DENGAN GANGGUAN JIWA - HERDAETHA, ADRIESTI (Jurnal Jurisprudence, 2015)
Criminal responsibility is an important factor in criminal offense. Determining a criminal responsibility of people with mental disorders is problematic. Mental disorders affect free will because they can affect oneâs ability to determine his or her alternative action. This juridical normative research studied the correlation between mental disorders and criminal behaviors, the criminal responsibility of people with mental disorders, and the settlement of criminal offense done by people with mental disorders at the investigation phase and before the court. Nearly all of mental disorders are related to criminal behaviors because they affect reasoning abilities. According to literatures, the mental condition that is most related to the criminal behaviors is automatisms: hallucination, illusion, and suspicion; impulse control disorders; personality disorders; mental retardation; and substance abuse.Â  On the evaluation of people with mental disorders, there is not solely one formulation applicable to all cases, but the there shall be a case-by-case review. Law and Psychiatrics have different concepts on the mental disorders.Â  Many law enforcement officers regard that all of people with mental disorders cannot be responsible. Law in Indonesia has a responsibility dichotomy, namely: irresponsible or fully responsible. There is a tendency that judges do not regard mental disorders as mitigating factors and do not include the elements of therapy in the verdict for people with mental disorders.